Non-Academic Achievement Improvement Through Extracurricular - Devi, Aulia Diana; Na’imah, Na’imah; Dinana, Aqimi (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2021)
Extracurricular activities are one of the containers in coaching and developing students' potential. This study aims to find out the management of extracurricular activities in improving the non-academic achievement of students in Madrasah Aliah Negeri 1 Tulang Bawang Barat. The method used is descriptive analysis using qualitative approach. This research conducts data collection techniques by observation, interviews, literature studies, and internet media. This study used primary data sources obtained through interviews and secondary data sources obtained through online media. The results showed that several steps in the management of extracurricular activities, such as planning, organizing, direction / implementation and evaluation as well as evaluation. Planning is carried out by investigating the number of extracurricular activities. Organizing is carried out by coordinating all components involved in the management of extracurricular activities. The implementation is carried out by arranging and arranging in writing so that the activities carried out can be directed and run smoothly in accordance with the guidelines. And the evaluation is done through member meetings and final assessments.